1992
DOI: 10.1172/jci116078
|View full text |Cite
|
Sign up to set email alerts
|

Human milk mucin inhibits rotavirus replication and prevents experimental gastroenteritis.

Abstract: Acute gastrointestinal infections due to rotaviruses and other enteric pathogens are major causes of morbidity and mortality in infants and young children throughout the world. Breastfeeding can reduce the rate of serious gastroenteritis in infants; however, the degrees of protection offered against rotavirus infection vary in different populations. The mechanisms associated with milk-mediated protection against viral gastroenteritis have not been fully elucidated.We have isolated a macromolecular component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
212
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(218 citation statements)
references
References 58 publications
5
212
0
1
Order By: Relevance
“…30,31 However, there is clearly a complex relationship between maternal antibody titers at the time of immunisation and viral load that affects the neutralisation of live viral vaccines. It has been postulated that when there is an excess of maternal antibody, such as in rotavirus endemic settings, and/or low viral load, there may be inhibition of viral replication, and thus possibly of both B and T cell infant responses.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 However, there is clearly a complex relationship between maternal antibody titers at the time of immunisation and viral load that affects the neutralisation of live viral vaccines. It has been postulated that when there is an excess of maternal antibody, such as in rotavirus endemic settings, and/or low viral load, there may be inhibition of viral replication, and thus possibly of both B and T cell infant responses.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity against HRV infection of human lactadherin was first identified by Yolken et al (1992). Furthermore, a previous clinical study indicated a correlation between human lactadherin in breast milk and morbidity due to rotavirus gastroenteritis in young children (Newburg et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 98%
“…Human lactoferrin (apo-or Fe 3+ ), -lactalbumin, -lactoglobulin, human lactadherin, mucin, and immunoglobulin from milk could prevent rotavirus infection through the binding to structural viral protein VP4 [30,37,38,40,107,108]. Also, the antiviral activity of lactoferrin against adenovirus has been attributed to the interaction of the milk protein with viral capsid proteins [60,61,69].…”
Section: Binding To Structural Virus Proteins Prevent Virus Host Cellmentioning
confidence: 99%